2018
DOI: 10.3390/molecules23061488
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Resistance Mechanisms of Inhibitors to Mps1 C604Y Mutation via a Comprehensive Molecular Modeling Study

Abstract: Mono-polar spindle 1 (Mps1/TTK) represents a protein kinase reported to be vital for cell division processes and is generally regarded as an attractive target for the treatment of hepatocellular carcinoma, breast carcinoma, and colon cancer. However, the C604Y mutation has been linked to acquired resistance. Recently, three potential small-molecule inhibitors of Mps1 (i.e., reversine, NMS-P715, and its derivative Cpd-5) were reported for the C604Y mutation that exhibit significant resistance to NMS-P715 and Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(62 reference statements)
2
4
0
Order By: Relevance
“…This finding was also consistent with the previous study that when Mps1 binds with Cpd-5, the A-loop region of Mps1 C604Y changes into an outward-moving conformation, but not the Mps1 WT (Chen et al, 2018). Compared with the previous results, we also found that the P-loop had a slight conformational change (Chen et al, 2018), particularly in Mps1 I598F and Mps1 C604Y systems. Overall, these results indicated that mutation-induced conformational change might be the main driving force for the redistributed energies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was also consistent with the previous study that when Mps1 binds with Cpd-5, the A-loop region of Mps1 C604Y changes into an outward-moving conformation, but not the Mps1 WT (Chen et al, 2018). Compared with the previous results, we also found that the P-loop had a slight conformational change (Chen et al, 2018), particularly in Mps1 I598F and Mps1 C604Y systems. Overall, these results indicated that mutation-induced conformational change might be the main driving force for the redistributed energies.…”
Section: Resultssupporting
confidence: 93%
“…Cpd-5 (N-(2,6-diethylphenyl)-8-((2-methoxy-4-(4-methylpiperazin-1-yl)phenyl)amino)-1-methyl-4,5-dihydro-1H-pyrazolo[4,3h] quinazoline-3 carboxamide), a derivative of NMS-P715, has been reported to display higher potency toward Mps1 than NMS-P715, reversine, MPI-0479605 (Koch et al, 2016). Recently, Chen et al (2018) reported resistance mechanisms of inhibitors to Mps1 C604Y Mutation, however, it is not clear from the structures why other mutations (I531M, I598F, S611R) would cause resistance. Molecular dynamics (MD) simulations may be helpful to explain these resistance mutations by monitoring the dynamics of the protein and its interactions with bound inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The A-loop region of mutant systems showed an outward-moving conformation ( Figure 5A-5D). This finding was also consistent with the previous study that when Mps1 binds with Cpd-5, the A-loop region of Mps1 C604Y changes into an outward-moving conformation, but not the Mps1 WT (Chen et al 2018). Compared with the previous results, we also found that P-loop had a slight conformational change (Chen et al 2018), particularly in Mps1 I598F and Mps1 C604Y systems.…”
Section: The Overall Structural Propertiessupporting
confidence: 93%
“…Recently, Chen et al (Chen et al 2018) reported resistance mechanisms of inhibitors to Mps1 C604Y Mutation, however, it is not clear from the structures why other mutations (I531M, I598F, S611R) would cause resistance. Molecular dynamics (MD) simulations may be helpful to explain these resistance mutations by monitoring the dynamics of the protein and its interactions with bound inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising progress in the development of highly selective and potent TTK inhibitors, their clinical efficacy and/or safety results have not been disclosed yet. Additionally, several “laboratory-generated” mutations, e.g., Ile 531 → Met 531 (I531M), Ile 598 → Phe 598 (I598F), Cys 604 → Tyr 604 (C604Y), and Ser 611 → Gly/Arg 611 (S611G/R), were reported to mediate resistance against the current TTK inhibitors, although no such mutant was detected from clinical samples yet. This might not be strange because the “occupancy-driven” action mode of a kinase inhibitor would unavoidably result in drug-induced mutations in the kinase domain.…”
Section: Introductionmentioning
confidence: 99%